Promoter Information Management System - Lim, Kar Nee; Nureize Arbaiy, (Applied Information Technology And Computer Science, 2024)
Dade Gifting Sdn. Bhd. is a business experienced in giving cultural and holiday gifts. The organization currently uses WhatsApp groups to manage organizers and monitor activities and sales results. However, this manual approach is ineffective and error-prone, which causes limited data collection and analysis, time-consuming tracking processes, missing official employment documents, and misunderstandings. Therefore, a web-based Promoter Information Management System (PIMS) was built to help organizations overcome these barriers and expand their operations. User login and registration, attendance and task tracking, inventory management, sales and performance analysis, and employment paperwork are just some of the services that PIMS will offer. Following Agile methodology and tools like Visual Studio Code, XAMPP, and phpMyAdmin, the system is expected to improve promoter management, optimize business processes, and enhance business strategy. Thus, this system is expected to improve procedures, reduce expenses, improve customer satisfaction, and increase brand exposure, which contributes to a significant advancement of business expansion.